Ophthalmic Optics and Visual Function - Negishi, Kazuno (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Exploring quality of vision is one of the most important issues in modern ophthalmology, and research into ophthalmic optics and visual function is essential for making progress in this field. The present Special Issue aims to enlighten readers about the broad range of clinical research in the field of ophthalmic optics and visual function, mainly related to the anterior segment and myopia control. Submissions of original research articles were welcomed that highlight innovative findings with the potential to enhance the clinical capabilities of diagnosing and monitoring ophthalmic conditions and treatments especially of the anterior segment. Review articles of high interest were also considered for publication.